OPTIONS OF LONG-TERM CONTRACEPTIVE METHODS IN MARRIED WOMEN IN SOUTH SULAWESI (ANALYSIS OF IDHS 2017) - Rahmawati Azis; Akmal Mahmud; Syahmida Syahbuddin Arsyad (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2021)
The long-term contraceptive method is an effective method for preventing pregnancies. However, users of long-term contraceptive methods are considerably lower compared to those of non-long-term contraceptive methods in South Sulawesi. The research objective was to examine the determinants of choosing long-term contraceptive methods in South Sulawesi. This study used data from the 2017 Indonesia Demographic and Health Survey by analyzing 583 married women who were using contraception in South Sulawesi. A descriptive analysis was employed to estimate the prevalence of long-term contraceptive methods. Meanwhile, the Chi-square test and logistic regression analysis were used to identify the determinants of choosing long-term contraceptive methods. The results from the descriptive analysis showed about 18.9% of the sampled married women were long-term contraception users, among those were implant users (10.2%). More married women with higher education and more parity chose to use it. The better the knowledge about the type of contraception, the greater the chance to use long-term contraceptive methods. Women who were told about side effects, sources of government services, and free fees were significantly influenced to use long-term contraception. Women who received staff visits and visited health facilities were less likely to choose the long-term methods. This implies that contact with field oMKJPlong-term contraceptive methodslong-term contraceptive methodsfficers has not been able to motivate prospective acceptors to use . Improved education and knowledge, especially about types of contraception and side effects, are needed to increase women’s long-term contraception use alongside. The quality of services at free/subsidized costs also needs to be improved, and training should be given for capacity building, especially in communication skills, to family planning field officers.